2010
DOI: 10.1002/jemt.20872
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic characterization of nucleolus‐associated domains during hibernation

Abstract: The nucleolus represents a highly dynamic nuclear compartment involved in multiple functions and able to promptly respond to variations of metabolic needs. In the hibernator dormouse, which drastically modifies its metabolic activity during the seasonal cycle, the nucleolus undergoes structural and molecular changes during the torpor bouts; in particular, it shows many nucleoplasmic invaginations containing weakly contrasted areas of unknown nature. To analyze the molecular composition of these nucleolus-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…et al, 2007) considering that altered nucleolus structure and aggregation of RNA binding proteins into subnuclear particles has been reported during hibernation (Malatesta et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2007) considering that altered nucleolus structure and aggregation of RNA binding proteins into subnuclear particles has been reported during hibernation (Malatesta et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that storage at the cleavage stage could allow for immediate renewal of translation which fits with the need for the rapid activation of brown adipose metabolism to support thermogenesis that must begin instantly when arousal starts. Immunocytochemistry also revealed changes in the molecular composition of the nucleolus during hibernation (Malatesta et al, 2011). Ultrastructure analysis showed the appearance of nucleolus-associated domains during hibernation …”
Section: Reviewmentioning
confidence: 94%
“…When other nuclear bodies like Cajal bodies were found embedded into the nucleolus, their morphology was still recognizable. 11,12 Moreover, these foci are different also from the nucleolus-associated domains described by Malatesta et al 13 in tissues from hibernating mammals.…”
Section: Discussionmentioning
confidence: 70%